Investigation of the comorbidity of dissociative disorders in patients with bipolar disorder - Tekin, Atilla; Özdil Demiryürek, Esra; Güleken, Mehmet Diyaddin; Bakım, Bahadır; Özer, Ömer Akil; Karamustafalıoğlu, Oğuz (The European Research Journal, 2019)
Objective: The aim of this study was to investigate the comorbidity of dissociative disorders in patients with bipolar disorder. Methods: Fifty-one patients who are diagnosed with bipolar disorder in euthymic state and forty-nine healty controls were included in the study. The Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I), Structured Clinical Interview for DSM-IV Dissociative Disorders (SCID-D), Dissociative Experiences Scale (DES) and Childhood Trauma Questionnaire (CTQ-28) were administered to all participants with a sociodemographic form.Results: Mean DES and CTQ-28 total scores were statistically higher in patients group than control group (p < 0.001 and p < 0.001, respectively). Emotional abuse, emotional neglect, physical abuse, physical neglect and sexual abuse subscale scores of CTQ-28 were higher in patients group than healthy controls group (p = 0.002, p < 0.001, p = 0.005, p < 0.001 and p < 0.021, respectively). The rate of any dissociative disorder comorbidity was %35.4 in patients with bipolar disorder. The most frequent dissociative disorder in patient with bipolar disorder was depersonalization disorder (%17.6). There was a positive correlation between DES score and number of suicidal attempts (r=0.284). Negative correlations were found between DES score and age of disease onset, and CTQ-28 total score and age of disease onset (r=-0.332 and r=-0.291). Conclusion: Our results have shown that dissociative disorders may be frequently accompanied in patients with bipolar disorder. Dissociation and childhood traumatic events can be related with clinical features in patients with bipolar disorder.